A Retrospective Study of Esophageal Foreign Bodies in Children: Incidence, Management, and Complications in a Tertiary Care Center - Mehmood Ullah, Ikram Ullah, Naveed Ahmed, Muhammad Iqbal, Jamshed Khan, Wajih Ud Din Shinwari (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Esophageal foreign body (EFB) ingestion is a prevalent issue in pediatric emergency care, often leading to significant complications if not promptly addressed. Early intervention is crucial to avoid morbidity, such as esophageal perforation, mucosal injury, or mediastinitis. Objective: This study aims to evaluate the incidence, clinical presentation, management strategies, and complications associated with EFBs in a tertiary care pediatric hospital. Methods: We conducted a retrospective analysis of 252 pediatric patients diagnosed with EFBs between April 2022 and June 2023. Data on demographics, type of foreign body, location, clinical symptoms, management approach, and complications were collected and analyzed. Results: The majority of patients were male (65%), with a mean age of 4.5 years. Coins were the most commonly ingested foreign bodies (45%), followed by food bolus (30%) and sharp objects (15%). The upper esophagus was the most frequent site of impaction (60%). Endoscopic removal was successful in 90% of cases, while 10% required surgical intervention due to complications such as perforation and mediastinitis. Conclusion: Prompt diagnosis and intervention are essential for managing EFBs in children. Endoscopic techniques remain the gold standard, with surgical intervention required in complicated cases. Keywords: Esophageal foreign body, pediatric emergency, endoscopic removal, complications, tertiary care hospital.